INISIATIF KEAMANAN PERDAGANGAN DALAM KEBIJAKAN EKONOMI LUAR NEGERI AMERIKA SERIKAT - Toton Hartanto (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2013)
The research objective was to test the impact of security threat and economic threat against U.S to the choice of container security intiative (CSI) as the instrument of foreign policy of US in Global War on terrorism (GwoT). The analyze employed by this research was economic statecraft concept ( baldwin,1985) as the main theory . The literature review of the research was able to find existence of security threat and economic thread pushing US to put their choice on CSI as the economic Statecraft in the policy of GwoT, The research employed qualitative model in which the statistical data analysis used was logoistic regression and it was obtained proves that justified CSI as the economic statecraft , the different response coming out between countries against the target of CSI was influenced by the interest of their economics and the consideration of the benefit value of the trading relationship within long term period.